A Structured Rounding Proforma in the Hyper Acute Stroke Unit (HASU): A Quality Improvement Project. Issue 1 (18th January 2023) - Ludley, Alistair; Bahk, Anna; Al-Shihabi, Ahmed
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: Strokes affect 100, 000 patients annually in the United Kingdom. These patients are often complex and require multidisciplinary team input, hence why they are often treated within dedicated and highly specialized "hyper acute stroke units". However, such specialist care can prove challenging to recently qualified or more junior doctors, who may miss pertinent aspects of the history or examination within the daily patient rounding documentation. Building on evidence-based practice using structured rounds and checklists, this quality improvement aimed to improve adherence of documentation for 20 predetermined key components of a stroke round by introducing a structured daily stroke rounding proforma. Adherence to documentation for the 20 components improved with the introduction of the stroke rounding proforma, with seven components demonstrating statistically significant positive changes in documentation rates, p < .05. Qualitative feedback was collected to aid in the development and acceptability of the proforma. Our study concluded a structured daily stroke rounding proforma can improve adherence to documentation in stroke care. Chiefly, the proforma was of greatest benefit to junior members of the medical team, particularly as an aid memoire.